Digital Control of Electrical Drives - Vukosavic, Slobodan N.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Digital Control of Electrical Drives offers insight into electric drives and their usage in motion control environment. It provides links among electrical machine and control theory, practical hardware aspects, programming issues, and application-specific problems. The book prepares the reader to understand the key elements of motion control systems, analyze and design discrete-time speed and position controllers, set adjustable feedback parameters, and evaluate closed-loop performances. Basic engineering principles are used to derive the controller structure in an intuitive manner, so that designs are easy to comprehend, modify, and extend. Digital Control of Electrical Drives helps the reader acquire practical skills in designing discrete-time speed and position controllers. Each chapter is followed by a set of Matlab® and Simulink® tools which help readers master the phases of design, tuning, simulation, and evaluation of discrete time controllers, and foresee the effects of control solution on the overall motion control system. Readers will also understand the present performance limits of digital motion controllers.
Speed Control -- Basic Structure of the Speed Controller -- Parameter Setting of Analog Speed Controllers -- Digital Speed Control -- Digital Position Control -- The Position Controller with Integral Action -- Trajectory Generation and Tracking -- Torsional Oscillations and the Antiresonant Controller.
Keywords: Power electronics; Energy systems; Electronic circuits; Control engineering; Robotics; Mechatronics; Electrical engineering; Energy; Power Electronics, Electrical Machines and Networks; Energy Systems; Circuits and Systems; Control, Robotics, Mechatronics; Electrical Engineering; Energy, general